Redox modulation of NQO1 - Siegel, David; Dehn, Donna D.; Bokatzian, Samantha S.; Quinn, Kevin; Backos, Donald S.; Di Francesco, Andrea; Bernier, Michel; Reisdorph, Nichole; de Cabo, Rafael; Ross, David (PloS one, 2018)
NQO1 is a FAD containing NAD(P)H-dependent oxidoreductase that catalyzes the reduction of quinones and related substrates. In cells, NQO1 participates in a number of binding interactions with other proteins and mRNA and these interactions may be influenced by the concentrations of reduced pyridine nucleotides. NAD(P)H can protect NQO1 from proteolytic digestion suggesting that binding of reduced pyridine nucleotides results in a change in NQO1 structure. We have used purified NQO1 to demonstrate the addition of NAD(P)H induces a change in the structure of NQO1; this results in the loss of immunoreactivity to antibodies that bind to the C-terminal domain and to helix 7 of the catalytic core domain. Under normal cellular conditions NQO1 is not immunoprecipitated by these antibodies, however, following treatment with β-lapachone which caused rapid oxidation of NAD(P)H NQO1 could be readily pulled-down. Similarly, immunostaining for NQO1 was significantly increased in cells following treatment with β-lapachone demonstrating that under non-denaturing conditions the immunoreactivity of NQO1 is reflective of the NAD(P)+/NAD(P)H ratio. In untreated human cells, regions with high intensity immunostaining for NQO1 co-localize with acetyl α-tubulin and the NAD+-dependent deacetylase Sirt2 on the centrosome(s), the mitotic spindle and midbody during cell division. These data provide evidence that during the centriole duplication cycle NQO1 may provide NAD+ for Sirt2-mediated deacetylation of microtubules. Overall, NQO1 may act as a redox-dependent switch where the protein responds to the NAD(P)+/NAD(P)H redox environment by altering its structure promoting the binding or dissociation of NQO1 with target macromolecules.